Cross-Journal Variation in Abstract Writing: Bundle-Driven Move Analysis in Applied Linguistics - Nur Rizka Kadir; Aris Munandar (TRANSBAHASA, 2026)
This study examines how four-word lexical bundles function as indicators of rhetorical moves in research article abstracts from two applied linguistics journals representing different academic traditions: the Indonesian Journal of Applied Linguistics (IJAL) and Applied Linguistics (AL) by Oxford University Press. While previous studies have categorized bundles structurally and functionally, fewer have explored how they align with rhetorical moves across journal communities. Using a bundle-driven approach, with a specialized corpus, the Journal Abstracts of Applied Linguistics (JAAL) was compiled, comprising over 100,000 words from abstracts published between 2019 and 2025. Four-word sentence-initial bundles were extracted using AntConc 4.3.1 and analyzed with Hyland’s five-move abstract model. Findings show that clause-based bundles dominate in both IJAL (59%) and AL (80%), while PP-based bundles are least frequent in IJAL (7%), challenging earlier claims. Product bundles occur most often in IJAL (49%), whereas AL abstracts prioritize purpose bundles (46%) and use more flexible patterns, including self-mentions that perform multiple rhetorical roles. These differences reflect broader cultural and linguistic conventions in academic voice. The study demonstrates the link between lexical bundles and rhetorical moves and underscores implications for EFL instruction and genre-based writing pedagogy.